THE ROLE OF SYNCHRONOUS AND ASYNCHRONOUS MULTIMEDIA IN EFL LISTENING COMPREHENSION - Kabri Kabri; Budiyanto Budiyanto (PRODI PENDIDIKAN BAHASA INGGRIS INSTITUT PENDIDIKAN DAN BAHASA INVADA, 2023)
This research investigates the role of synchronous and asynchronous multimedia in EFL listening comprehension among EFL learners. The study adopts a mixed-methods design, gathering quantitative data through listening comprehension tests and surveys and qualitative data through focus group discussions and interviews. Participants from various proficiency levels engaged with both synchronous and asynchronous multimedia. The findings revealed significant improvements in EFL listening comprehension for learners exposed to both formats. Synchronous multimedia offered interactive experiences with immediate feedback, while asynchronous materials provided flexibility and autonomy. A blended approach accommodating diverse preferences proves beneficial for language educators, fostering well-rounded language proficiency in EFL learners worldwide.